Anesthesia-mediated neuroinflammatory sequelae in post operative cognitive dysfunction: mechanisms and therapeutic implications - Smith, Gregory T.; Chen, Tytus J.; Shah, Neha M.; Agrest, Brett; Grotticelli, Janet (Frontiers in Anesthesiology, 2024)
Post-operative cognitive dysfunction (POCD) is an iatrogenic cognitive decline with unclear etiology. While current hypotheses include surgical and pharmacological-induced neuroinflammatory mechanisms, the growing prevalence, especially amongst the geriatric population, emphasizes the ambiguity of the dysfunction. Recent studies have highlighted the potential role of general and regional anesthesia in the pathogenesis of POCD; these pharmacological effects have been demonstrated to disrupt blood-brain barrier integrity, influence microglial polarization, and have been linked to worsening prognoses in cognitive decline. Moreover, mechanical stress from surgical intervention and reperfusion injury may exacerbate the generation of reactive oxygen species (ROS), thereby increasing oxidative stress to the brain synergistically with blood-brain barrier disruptions. In previous studies, factors for the variable incidence and various risk factors have been explored. In this review, we examine the pharmacological effects of local, regional, and general anesthesia on molecular and cellular glial response, along with its intercellular interactions and previously reported clinical outcomes.